Tolerogenic dendritic cells and TLR4/IRAK4/NF-κB signaling pathway in allergic rhinitis - Kang, Chenglin; Li, Xiaomei; Liu, Peng; Liu, Yue; Niu, Yuan; Zeng, Xianhai; Zhao, Hailiang; Liu, Jiangqi; Qiu, Shuqi (Frontiers in Immunology, 2023)
Dendritic cells (DCs), central participants in the allergic immune response, can capture and present allergens leading to allergic inflammation in the immunopathogenesis of allergic rhinitis (AR). In addition to initiating antigen-specific immune responses, DCs induce tolerance and modulate immune homeostasis. As a special type of DCs, tolerogenic DCs (tolDCs) achieve immune tolerance mainly by suppressing effector T cell responses and inducing regulatory T cells (Tregs). TolDCs suppress allergic inflammation by modulating immune tolerance, thereby reducing symptoms of AR. Activation of the TLR4/IRAK4/NF-κB signaling pathway contributes to the release of inflammatory cytokines, and inhibitors of this signaling pathway induce the production of tolDCs to alleviate allergic inflammatory responses. This review focuses on the relationship between tolDCs and TLR4/IRAK4/NF-κB signaling pathway with AR.